11-1 Mt. Vernon Street, ca. 1870-89 - Unknown (Tufts Archival Research Center, 2005)
Street-level view north-northeast of (left to right) 11-1 Mt. Vernon Street, located between Beacon Street to the south and Mt. Vernon Street to the north. Wrought-iron railing adorns the facades of 1-11 Mt. Vernon Street, which face west towards the Massachusetts State House. The facades of (right to left) 13 and 15 Mt. Vernon Street face south and are visible in the background of the photograph. The southeast corner of the Massachusetts State House is included along the left side of the photograph. A woman walks on the sidewalk along the west side of Mt. Vernon Street. A horse-drawn carriage waits at the southwest corner of Beacon and Mt. Vernon Streets, while a second carriage is located on Beacon Street near Park Street. 7 1/2 x 9 1/2, 7 13/16 x 9 3/4 overall Photographs